Effects of Different Grazing Disturbances on the Plant Diversity and Ecological Functions of Alpine Grassland Ecosystem on the Qinghai-Tibetan Plateau - Li, Wenlong; Liu, Chenli; Wang, Wenying; Zhou, Huakun; Xue, Yating; Xu, Jing; Xue, Pengfei; Yan, Hepiao (Frontiers in Plant Science, 2021)
Grazing is one of the main human disturbance factors in alpine grassland on the Qinghai-Tibet Plateau (QTP), which can directly or indirectly influence the community structures and ecological functions of grassland ecosystems. However, despite extensive field grazing experiments, there is currently no consensus on how different grazing management approaches affect alpine grassland diversity, soil carbon (C), and nitrogen (N). Here, we conducted a meta-analysis of 70 peer-reviewed publications to evaluate the general response of 11 variables related to alpine grassland ecosystems plant diversity and ecological functions to grazing. Overall, the results showed that grazing significantly increased the species richness, Shannon-Wiener index, and Pielou evenness index values by 9.89% (95% CI: 2.75%–17.09%), 7.28% (95% CI: 1.68%–13.62%), and 3.74% (95% CI: 1.40%–6.52%), respectively. Aboveground biomass (AGB) and belowground biomass (BGB) decreased, respectively by 41.91% (95% CI: -50.91% to -32.88%) and 17.68% (95% CI: -26.94% to -8.52%). Soil organic carbon (SOC), soil total nitrogen (TN), soil C:N ratio and soil moisture decreased by 13.06% (95% CI: -15.88% to -10.15%), 12.62% (95% CI: -13.35% to -8.61%), 3.27% (95% CI: -4.25% to -2.09%), and 20.75% (95% CI: -27.89% to -13.61%), respectively, whereas, soil bulk density and soil pH increased by 17.46% (95% CI: 11.88%–24.53%) and 2.24% (95% CI: 1.01%–3.64%), respectively. Specifically, moderate grazing, long-durations (>5 years), and winter grazing contributed to increases in the species richness, Shannon-Wiener index, and Pielou evenness index. However, AGB, BGB, SOC, TN, and soil C:N ratios showed a decrease with enhanced grazing intensity. The response ratio of SOC was positively associated with AGB and BGB but was negatively related to the Shannon-Wiener index and Pielou evenness index. Furthermore, the effects of grazing on plant diversity, AGB, BGB, SOC, and TN in alpine grassland varied with grazing duration, grazing season, livestock type, and grassland type. The findings suggest that grazing should synthesize other appropriate grazing patterns, such as seasonal and rotation grazing, and, furthermore, additional research on grazing management of alpine grassland on the QTP is needed in the future.